2012
DOI: 10.1089/jwh.2011.3222
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Influence Obstetrician-Gynecologists to Follow Recommended HIV Screening and Testing Guidelines?

Abstract: The results of this study suggest that the provider's perception about the patients' risk for being infected as well as practice type and location are important factors influencing an obstetrician-gynecologist's decision to screen a nonpregnant woman for HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…10 Since 2007, results from representative surveys of health care workers, including obstetricians/gynecologists (OB/GYNs) providing care to women who were not pregnant, osteopaths, internal medical residents in New York City (NYC) and physicians, nurse practitioners, physician assistants, and midwives in general internal medicine, showed that only up to one-quarter offered HIV testing in compliance with CDC guidelines. 7,13,14,15 The practice of routine HIV testing varies by physician characteristics. OB/GYNs are more likely to report the practice of routine HIV testing in the post-2006 period, presumably since screening of pregnant women for HIV has been CDC's standard of care since 2001.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Since 2007, results from representative surveys of health care workers, including obstetricians/gynecologists (OB/GYNs) providing care to women who were not pregnant, osteopaths, internal medical residents in New York City (NYC) and physicians, nurse practitioners, physician assistants, and midwives in general internal medicine, showed that only up to one-quarter offered HIV testing in compliance with CDC guidelines. 7,13,14,15 The practice of routine HIV testing varies by physician characteristics. OB/GYNs are more likely to report the practice of routine HIV testing in the post-2006 period, presumably since screening of pregnant women for HIV has been CDC's standard of care since 2001.…”
Section: Introductionmentioning
confidence: 99%
“…OB/GYNs are more likely to report the practice of routine HIV testing in the post-2006 period, presumably since screening of pregnant women for HIV has been CDC's standard of care since 2001. 11,13,14 In contrast, pediatricians seem to be the least likely to routinely offer HIV testing to their patients and tend to view testing for HIV as a lower priority than other adolescent issues, such as sexually transmitted infections, violence, or substance abuse. 16,17 Researchers have found that female physicians seem more willing to adopt routine HIV testing practices, 7,8,11,16,17 as are younger practitioners 11,17 and those who completed training within the past 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations